A formative intervention for developing Learner Representative Council (LRC) voice and leadership in a newly established school in Namibia - Amadhila, Linda (Rhodes University, Faculty of Education, Department of Education, 2018)
In Namibian schools, learner voice and leadership are being promoted through the policy document entitled the Education Act 16 of2001 which provides an opportunity to establish Learner Representative Councils (LRCs) in secondary schools. However, recent studies have found that this body of learner leaders do not function all that effectively and sometimes exist for the sake of adhering to the policy. This prompted me to conduct an activity theoretical interventionist case- study within the critical paradigm, to develop LRC voice and leadership in a newly established Namibian school. Framed by Cultural Historical Activity Theory, the study was divided into two phases to answer the over-arching question: How can LRC voice and leadership be developed in a school? Phase one was largely interpretive, the contextual profiling phase, where document analysis, individual interviews, questionnaires and observations were used to generate data to answer the following research sub-questions: How is learner leadership understood in the school? What leadership development opportunities for the LRC currently exist in the school? What underlying factors constrain the development of LRC voice and leadership in the newly established school? Phase two of the study was the expansive learning phase, which consisted of three intervention workshops. The Change Laboratory method and a focus group interview were used to generate data in response to the last research sub-question: In what ways can LRC participation in a Change Laboratory process contribute to their leadership development? Data generated were inductively and deductively analysed, using the activity theoretical principles of contradictions and double stimulation. Data revealed that learner leadership was largely understood as managerial roles carried out by the LRC in the school. Unlike many schools in Namibia, this case-study school offered numerous leadership development opportunities for the LRC. The community networking events such as: School Exchange Programmes, Town Council breakfast and Junior Regional Council, were opportunities offered to the LRC to solicit information, exchange ideas and discuss matters of common interest with the LRCs of the fully established schools. However, there were a number of challenges that constrained LRC voice and leadership development, the major one being the fact that this was a newly established school. Of significance was that LRC participation in the Change Laboratory process contributed positively to the development of voice and leadership in learners. During this Change Laboratory process, the LRC developed a new artefact - the vision and mission statement of the school - this signified that the learners expansively transformed the object of their activity. Recommendations emerging out of the study included that the School Management Team see the 'newly established' status of the school as an opportunity for development, rather than a limitation, and therefore invite the LRC to participate in the different leadership practices as the school becomes established. A significant recommendation for school leadership research is to use the third generation of CHAT to expand the unit of analysis, in order to understand the leadership relations and power dynamics between multiple activity systems in schools as complex organisations.
Keywords: School management and organization -- Namibia; Educational leadership -- Namibia; Education, Secondary -- Namibia; Student government -- Namibia; Student participation in administration -- Namibia